Prediction of Difficulties in Emotion Regulation Based on Internal Locus of Control with the Mediating Role of Emotion-Focused Coping Strategies in Infertile Women - Mahmoodi Mozafar , Majid; Mohebi , Mohammad; Feyzbakhsh Vaghef, Maryam (Psychology of Woman Journal, 2026)
Objective: The present study aimed to predict difficulties in emotion regulation based on internal locus of control through the mediating role of emotion-focused coping strategies among infertile women in Tehran.Methods and Materials: This research employed a descriptive–correlational design using structural equation modeling (SEM). The statistical population consisted of infertile women referring to infertility treatment centers in Tehran in 2025. Based on Krejcie and Morgan’s sample size determination table, 400 participants were selected through convenience sampling. Data were collected using standardized instruments: the Difficulties in Emotion Regulation Scale (DERS; Gratz & Roemer, 2004), the Rotter’s Internal–External Locus of Control Scale (Rotter, 1966), and the Coping Inventory for Stressful Situations (CISS; Endler & Parker, 1990). Data analysis was performed using SPSS-27 for descriptive and correlational statistics and AMOS-21 for structural equation modeling. Model fit was evaluated using χ²/df, GFI, AGFI, CFI, TLI, and RMSEA indices.Findings: Results showed that internal locus of control was significantly and negatively correlated with difficulties in emotion regulation (r = –.48, p < .001) and emotion-focused coping (r = –.36, p < .001), while emotion-focused coping was positively correlated with difficulties in emotion regulation (r = .42, p < .001). The SEM results confirmed that internal locus of control had a direct negative effect on emotion regulation difficulties (β = –0.33, p < .001) and an indirect effect through emotion-focused coping (β = –0.14, p < .01). The model fit indices (χ²/df = 1.73, GFI = 0.94, CFI = 0.96, RMSEA = 0.042) indicated an excellent model fit.Conclusion: Internal locus of control plays a crucial protective role in reducing emotional regulation difficulties among infertile women, both directly and indirectly, through the regulation of emotion-focused coping strategies. Strengthening internal control beliefs and promoting adaptive emotional coping can enhance psychological resilience in infertility-related distress.